KESIAPSIAGAAN PENDUDUK PADA BENCANA BANJIR DI KELURAHAN CEMPAKA PUTIH BARAT KECAMATAN CEMPAKA PUTIH KOTA JAKARTA PUSAT - Maulana, Adhitya Rizky; Fadiarman, Fadiarman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Determination of Flood Preparedness Level in Cempaka Putih Barat Village, Cempaka Putih Village, Central Jakarta City, this research is descriptive and the population in this study is people living in Cempaka Putih Barat District. This west white cempaka village consists of 13 community units totaling 13,137 households, the number of samples taken is based on the number of affordable populations, which is 1,242 households because the human samples collected are household actors represented in household units, So this research will focus on knowledge and attitudes, emergency planning, disaster warning systems, and resource mobilization using a disaster risk reduction formula using four parameters.